A pilot digital mammography database establishment and entrance skin exposure evaluation / Juma’atun Sima Hasim - Hasim, Juma’atun Sima (2013)
A digital mammography database is important for image storage, retrieval and teaching purposes. An attempt is made to establish a pilot digital mammography image database to be used together with computed assisted diagnosis (CADG) software for early breast cancer detection in Malaysia. The main objective of this study is to establish a pilot digital mammography image database system. A total of 736 images of patients undergoing digital mammography examination were collected. All of the images were loaded into the database using the MATLAB platform. The ESE between digital and conventional mammography was also measured. ESE was obtained by using thermoluminescent dosimeter (TLD), ionization chamber and the mammography phantom RMI 156. The exposure factors for each patient in digital mammography were recorded. The same procedures were then simulated by phantom study for both conventional and digital mammography. The exposure parameters and ESE measurements from conventional and digital systems were compared using independent /-test. The results showed no significant difference for comparisons of ESE values of conventional and digital mammography and ESE values of mediolateral oblique (MLO) and craniocaudal (CC) views. A significant difference was resulted from comparison of ESE, mAs and kVp of different breast density. The important contents of the proposed database system were identified which comprised of patient file, report file, mammography report, Breast Imaging Reporting and Data System (BIRADS), mammography images, dose and additional screening. The proposed database can be improved by using other database software. Further study should be carried out by including a large sample size for the ESE measurement.